Clinical characterization of two severe cases of hemorrhagic fever with renal syndrome (HFRS) caused by hantaviruses Puumala and Dobrava-Belgrade genotype Sochi. Issue 1 (December 2016) - Krautkrämer, Ellen; Nusshag, Christian; Baumann, Alexandra; Schäfer, Julia; Hofmann, Jörg; Schnitzler, Paul; Klempa, Boris; Witkowski, Peter; Krüger, Detlev; Zeier, Martin
Abstract Background Hantavirus disease belongs to the emerging infections. The clinical picture and severity of infections differ between hantavirus species and may even vary between hantavirus genotypes. The mechanisms that lead to the broad variance of severity in infected patients are not completely understood. Host- and virus-specific factors are considered. Case presentation We analyzed severe cases of hantavirus disease in two young women. The first case was caused by Puumala virus (PUUV) infection in Germany; the second case describes the infection with Dobrava-Belgrade virus (DOBV) in Russia. Symptoms, laboratory parameters and cytokine levels were analyzed and compared between the two patients. Serological and sequence analysis revealed that PUUV was the infecting agent for the German patient and the infection of the Russian patient was caused by Dobrava-Belgrade virus genotype Sochi (DOBV-Sochi). The symptoms in the initial phase of the diseases did not differ noticeably between both patients. However, deterioration of laboratory parameter values was prolonged and stronger in DOBV-Sochi than in PUUV infection. Circulating endothelial progenitor cells (cEPCs), known to be responsible for endothelial repair, were mobilized in both infections. Striking differences were observed in the temporal course and level of cytokine upregulation. Levels of angiopoietin-2 (Ang-2), vascular endothelial growth factor (VEGF), and stromal derived factor-1 (SDF-1α) were increased in both infections; but, sustained and more pronounced elevation was observed in DOBV-Sochi infection. Conclusions Severe hantavirus disease caused by different hantavirus species did not differ in the general symptoms and clinical characteristics. However, we observed a prolonged clinical course and a late and enhanced mobilization of cytokines in DOBV-Sochi infection. The differences in cytokine deregulation may contribute to the observed variation in the clinical course.